What you exported matters: Persistence in productive capabilities across two eras of globalization - Isabella Weber; Gregor Semieniuk; Tom Westland; Junshang Liang (University of Massachusetts, Department of Economics, 2021)
Does what you exported matter? We build a new global commodity-level export database for the previous era of globalization and find persistence in productive capabilities proxied by economic complexity, export diversification, and sophistication across a century. We also show that productive capabilities at the turn of the 20th century are a powerful predictor of today's income levels. We demonstrate that our results are not driven by persistence in geography or institutions. The persistence mechanism is the complementarity between past and future productive capabilities with one important qualification, the persistent negative effect of European overseas colonization. We also study shocks that undermined persistence, confirm the resource course hypothesis for the long run and find a positive but slow effect of democratization.
Keywords: F14; F63; N10; O10; O50; 330; Export; Produktivität; Globalisierung; Welt